The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/masy.201600155
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite Nanotubes Filled in Asymmetric Blend of Polyamide 6, 12/poly (Ethylene‐Octene) Elastomer: Tough‐to‐Brittle Transition in Nanocomposites

Abstract: Summary A tough‐to‐brittle transition is distinctly observed with a critical correspondence to dispersed phase domain size in halloysite nanotubes filled ternary nanocomposites based on compositionally asymmetric and toughened blend of polyamide 6, 12 (PA‐6, 12)/poly(ethylene‐octene) copolymer‐g‐maleic anhydride (POE‐g‐MA) as the matrix. The maxima in the resistance to fracture initiation and crack propagation resistance normalized fracture initiation as a measure of toughness followed by a significant drop wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…[39] There are several studies using EWF, to study the fracture characteristic of polymer nanocomposites based on polyamide/POE-g-MA. For example, Kumar et al [40] studied the effect of halloysite nanotube (HNT) on the fracture characteristic of PA612/POE-g-MA via the EWF method. Kumar concluded that, with a growth in the content of HNT in PA612/POE-g-MA compounds, the essential work of fracture enhanced and then decreased.…”
Section: Introductionmentioning
confidence: 99%
“…[39] There are several studies using EWF, to study the fracture characteristic of polymer nanocomposites based on polyamide/POE-g-MA. For example, Kumar et al [40] studied the effect of halloysite nanotube (HNT) on the fracture characteristic of PA612/POE-g-MA via the EWF method. Kumar concluded that, with a growth in the content of HNT in PA612/POE-g-MA compounds, the essential work of fracture enhanced and then decreased.…”
Section: Introductionmentioning
confidence: 99%